Aromaterapi Lavandula Angustifolia untuk Mempercepat Durasi Persalinan - Kundarti, Finta Isti; Titisari, Ira; Yanuarini, Triatmi Andri; Nurlaili, Anis; Esyuananik, Esyuananik (Poltekkes Kemenkes Bandung, 2026)
Background: Prolonged labor is one of the causes of maternal and neonatal mortality. Lavandula angustifolia aromatherapy has the potential to increase labor duration. Objective: This study aimed to analyze the effect of Lavandula angustifolia aromatherapy on the duration of the first stage of active labor. Methods: This type of research was quantitative with a posttest-only design with a control group, using simple random sampling. The study was conducted from May to July 2023 at Kediri City Hospital with a sample size of 60 participants giving birth in the active phase at Kediri City Hospital, with an intervention group of n = 30 and a control group of n = 30. In the intervention group, respondents were given Lavandula angustifolia aromatherapy through inhalation during the active phase of labor, accompanied by standard care according to hospital procedures. In the control group, respondents only received standard care. Duration assessment was carried out from 4-10 cm dilation. Results: The results were tested using a t-test, showing that the average duration of labor in the intervention group VS the control group was m = 292.50 (13,975) minutes versus m = 374.70 (16,572) minutes with a p value of 0.000. Conclusion: The results of this study indicate that the duration of the first stage of active labor in the intervention group was shorter than that of the control group after administration of Lavandula Angustifolia Aromatherapy. This study can be a recommendation for midwives to provide Lavandula Angustifolia Aromatherapy as a safe and effective intervention in accelerating the duration of labor.